Braemar... : bila perempuan tua dan anak muda bangkit - Arutchelvan, S.; Parti Sosialis Malaysia (Petaling Jaya, Selangor : Gerakbudaya Enterprise, 2013)
On issue of land use and labor in Breamar Estate, Selangor, Malaysia.
In Malay and English.
Keywords: Tamil (Indic people) -- Malaysia -- Social conditions; Right to labor; Right to housing